An investigation of the acute behavioural effects of styrene on factory workers. - Cherry, N (1980)
A group of men exposed to styrene in a factory building glass-fibre boats performed a series of behavioural tests at the beginning and end of their shift, and the results were compared with those of a referent group from the same factory. Changes in mood were noted in both groups of workers but were greater in the exposed men; moreover, the change in mood was correlated with blood styrene concentration. In the styrene workers the morning reaction time was slower than that for the referents. During the day the reaction time of the men with low blood styrene concentration (less than or equal to 5.4 mumol/l) speeded up and in the afternoon was similar to that of the referents; the reaction time for the men with high blood styrene concentration (greater than or equal to 5.5 mumol/l) was unchanged. Data taken from a questionnaire indicated that the men exposed were much more likely than was the referent group to report feeling unduly tired. They also reported feeling more tired on Friday night than Monday night, suggesting that the styrene might have a cumulative effect through the week.